2009
DOI: 10.1155/2009/917623
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive and Rapid Real-Time PCR Analysis of 21 Foodborne Outbreaks

Abstract: A set of four duplex SYBR Green I PCR (SG-PCR) assay combined with DNA extraction using QIAamp DNA Stool Mini kit was evaluated for the detection of foodborne bacteria from 21 foodborne outbreaks. The causative pathogens were detected in almost all cases in 2 hours or less. The first run was for the detection of 8 main foodborne pathogens in 5 stool specimens within 2 hours and the second run was for the detection of other unusual suspect pathogens within a further 45 minutes. After 2 to 4 days, the causative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…A range of PCR assays targeting different genomic fragments have been developed for the detection of P. shigelloides (Table 9) (42,51,221,222,223,224,225). One of the earliest assays was configured by González-Rey et al (42) and targeted a specific variable region of the 23S rRNA gene previously identified by Van Camp et al (226).…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of PCR assays targeting different genomic fragments have been developed for the detection of P. shigelloides (Table 9) (42,51,221,222,223,224,225). One of the earliest assays was configured by González-Rey et al (42) and targeted a specific variable region of the 23S rRNA gene previously identified by Van Camp et al (226).…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
“…This is an advance on 16S rRNA sequencing, where P. shigelloides previously showed a closer affinity with species of the Enterobacteriaceae than with the Aeromonadaceae (19). The gyrB gene has also been used as a target in a PCR assay to detect P. shigelloides in investigations of foodborne outbreaks (223,224).…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
“…Real-time PCR (qPCR) assays have gained confidence as faster and reliable alternatives (Postollec et al 2011 ), and several qPCR assays have already been developed (e.g. Beutin et al 2009 ; Botteldoorn et al 2003 ; Fukushima et al 2009 ; Garrido et al 2012b ; Kim and Cho 2010 ; Löfström et al 2010 ; Singh et al 2012 ). However, their use all together into the same detection system is hampered by several drawbacks: they are using different technologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…7 LNA probes have recently been used to differentiate between the same species (a wild-type and a mutant) with a single base mutation 8 and have also been employed in food-safety-based assays. 7 RT-PCR has been widely used to recognize unwanted materials or contaminants in foods, including pathogens, 9,10 allergens, 11−13 and other unexpected products. 14−16 Designing RT-PCR assays for the identification of closely related species of plants is challenging because there is often little or no differentiation in the gene regions typically used to identify plants.…”
Section: ■ Introductionmentioning
confidence: 99%